Os desafios e as possibilidades de melhoria da política municipal de segurança pública: estudo de caso de roubo e furto na cidade de Gurupi-TO - Disconzi (Universidade Federal do Tocantins, 2019)
Public Security has been debated from the earliest days and, throughout history, countries have come together with the intention of signing international agreements to rescue social peace. It is one of the rights, guaranteed to all, by the federal constitution of 1988, however, the sense of insecurity has affected citizens and cities, a fact that has led the discussions on the importance of strengthening public mechanisms for the prevention and fight against crime. The present work deals with the crimes of robberies and thefts of commercial, residential, passerby, among others. It presents national, state and municipal data from Gurupi, Tocantins and analyzes the variations of the records, in the 2014-2015 and 2016-2017 biennia. It uses secondary data collected by the IPEA, the State Military Police and the 4th Battalion of the Gurupi Military Police. It compares the theft and robbery records in Gurupi to demonstrate the variations of the insecurity indexes in this municipality and to verify what policies could be added to the public entity in order to seek a reduction in robbery and robbery crimes. It analyzes these data in the light of the conception that the State needs to rescue the role of protector of the whole nation, breaking the vicious circle of physical and psychological punishment for those convicted of crimes. As main results, it should be noted that, in the second biennium, there was an increase of 72.98% in residential thefts. The robbery of passersby had a reduction of 3.05% in the same period, but nevertheless, represents the second nature of crime with greater incidence. The other two crimes that deserve attention are theft of vehicle (which had an increase of 5.85%), and robbery in residence (with an increase of 53.93%). It is observed, in view of the current situation, the need for a public policy that can meet all these peculiarities and concludes that the most appropriate measure to meet the needs of the city of Gurupi is the completion of a Restorative Justice Project.